Identification of possible source markers in marine dissolved organic matter using ultrahigh resolution mass spectrometry - Kujawinski, Elizabeth B.; Longnecker, Krista; Blough, Neil V.; Vecchio, Rossana Del; Finlay, Liam; Kitner, Joshua B.; Giovannoni, Stephen J. (Geochimica et cosmochimica acta, 2009)
Marine dissolved organic matter (DOM) is one of the most heterogeneous and largest pools of reactive carbon on earth, rivaling in mass the carbon in atmospheric carbon dioxide. Nevertheless, the molecular-level composition of marine DOM has eluded detailed description, impeding inquiry into the specific mechanisms that add or remove compounds from the DOM pool. Here we describe the molecular-level composition of C 18-extracted DOM along an east–west transect of the North Atlantic Ocean. We examine the changes in DOM composition along this transect with ultrahigh resolution mass spectrometry and multivariate statistics. We use indicator species analysis (ISA) to identify possible source markers for photochemical degradation and heterotrophic bacterial metabolism. The inclusion of ISA in statistical evaluation of DOM mass spectral data allows investigators to determine the m/z values associated with significant changes in DOM composition. With this technique, we observe indicator m/z values in estuarine water that may represent components of terrestrially-derived chromophoric DOM subject to photochemical degradation. We also observe a unique set of m/z values in surface seawater and show that many of these are present in pure cultures of the marine α-proteobacterium ‘‘ Candidatus Pelagibacter ubique” when grown in natural seawater. These findings indicate that a complex balance of abiotic and biotic processes controls the molecular composition of marine DOM to produce signatures that are characteristic of different environments.